Introduction to mathematical statistics - Messikh Azeddine, Azeddine (2016)
This is the course taught to second year students during the semester 1 2016/2017 at Department of Computer Science, Kulliyyah of Information and Communication Technology, International Islamic University Malaysia. This is the last semester this course is offered. This course is an introductory to mathematical statistics. It is based on the textbook: Introduction to Mathematical Statistics and Its Applications by Richard J. Larsen and Morris L. Marx. We focus on random variables, estimation, and hypothesis testing. We also show how to simulate some of the probability density functions using R language which is an open source and can be downloaded for free.